1991
DOI: 10.2307/30146936
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Transmission and Infection Control Aspects of Parasitic and Ectoparasitic Diseases Part III. Ectoparasites/Summary and Conclusions

Abstract: As a rule, both the standard of hygiene and sanitation prevalent in hospitals in the United States and the rarity of parasitic diseases compared to viral, bacterial, and fungal infections, reduce the hazard of nosocomial acquisition of parasites to relatively trivial levels. However, abetted by the resultant low index of suspicion on the part of clinical staff, certain parasitic microorganisms may at times cause significant morbidity and even mortality in both normal and immunocompromised patients, as summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…The present scabies epidemic in Japan began around 1975 and continues mostly in institutional settings such as nursing homes, long-term care hospitals and psychiatric hospitals. [1][2][3] Various factors have contributed to the outbreak of scabies in institutions: delay of diagnosis, misuse of corticosteroid and iatrogenic crusted scabies, 4 increased number of immunocompromised hosts due to population aging, and frequent patient transfers among hospitals. 5 Through investigations on institutional scabies outbreaks, we have found that a considerable number of patients suffer from recurrence of scabies.…”
Section: Introductionmentioning
confidence: 99%
“…The present scabies epidemic in Japan began around 1975 and continues mostly in institutional settings such as nursing homes, long-term care hospitals and psychiatric hospitals. [1][2][3] Various factors have contributed to the outbreak of scabies in institutions: delay of diagnosis, misuse of corticosteroid and iatrogenic crusted scabies, 4 increased number of immunocompromised hosts due to population aging, and frequent patient transfers among hospitals. 5 Through investigations on institutional scabies outbreaks, we have found that a considerable number of patients suffer from recurrence of scabies.…”
Section: Introductionmentioning
confidence: 99%
“…Fecal pellets dissolve easily with potassium hydroxide and can be stained with chlorazol black E. 39 At present, there is no established method for differentiating whether the mite is alive or dead. 40,41 Even in cases of eruption associated with scabies, the mite detection rate with microscopy varies widely, ranging 10-70%, 17,[42][43][44] so it is essential to improve the techniques of detection and to frequently repeat the test at different sites on the body. For efficient detection of S. scabiei, the mite burrows must be magnified with a dermoscope and the tips of the burrows examined.…”
Section: Microscopymentioning
confidence: 99%
“…However, even with epidemiological studies, it is often impossible to identify the crusted scabies that are the source of infection. 44,134,135 Patients with crusted scabies are often in poor general health, and may leave the affected group before diagnosis due to death or hospital transfer, so the affected person may be absent at the time the mass outbreak is recognized. In these situations, the patient first diagnosed with common scabies may be erroneously regarded as the source of infection.…”
Section: Basic Concept Of Scabies Preventionmentioning
confidence: 99%
“…14,24,25 Even in cases of eruption associated with scabies, the mite detection rate with microscopy varies widely (10-60%) among reports. [26][27][28] It is therefore desirable to improve the techniques of detection and to conduct the test on multiple parts of each case. For efficient detection of mites (particularly in elderly individuals), it is essential to check carefully for burrows (formed along the folds of palm or planta) and the V-shaped wake-like scales.…”
Section: Microscopymentioning
confidence: 99%